2024
DOI: 10.18632/aging.205547
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between gut microbiota and risk of esophageal cancer: evidence from Mendelian randomization study

Kui Wang,
Jiawei Wang,
Yuhua Chen
et al.

Abstract: Background: The causative implications remain ambiguous. Consequently, this study aims to evaluate the putative causal relationship between gut microbiota and Esophageal cancer (EC). Methods: The genome-wide association study (GWAS) pertaining to the microbiome, derived from the MiBioGen consortium-which consolidates 18,340 samples across 24 population-based cohorts-was utilized as the exposure dataset. Employing the GWAS summary statistics specific to EC patients sourced from the GWAS Catalog and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Another study provided further evidence that remodeling the gut microbiota by restoring dysbiosis characterized by the presence of genus Eubacterium nodatum group and other relevant bacterial genera effectively improved the disruption of the gut-brain barrier, thereby providing a potential therapeutic approach for the treatment of cerebral ischemic stroke ( Chen et al, 2019 ). The genus Ruminococcaceae UCG011 and genus Ruminococcaceae UCG010 , belonging to family Ruminococcaceae , have been reported as associated with some diseases such as leukemia ( Chen et al, 2023 ), type 2 diabetes ( Li and Li, 2023 ), and esophageal cancer ( Wang et al, 2024 ), but they have yet to be studies in the context of mental health disorders. However, multiple clinical studies have demonstrated that psychological distress and mental illness, such as depression and anxiety, are associated with alterations in the abundance of Ruminococcaceae family members ( Chen et al, 2021 ; Chin Fatt et al, 2023 ), and animal studies have suggested that regulating the abundance of Ruminococcaceae family members with various interventions can promote the production of SCFAs and other neurochemical-related metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Another study provided further evidence that remodeling the gut microbiota by restoring dysbiosis characterized by the presence of genus Eubacterium nodatum group and other relevant bacterial genera effectively improved the disruption of the gut-brain barrier, thereby providing a potential therapeutic approach for the treatment of cerebral ischemic stroke ( Chen et al, 2019 ). The genus Ruminococcaceae UCG011 and genus Ruminococcaceae UCG010 , belonging to family Ruminococcaceae , have been reported as associated with some diseases such as leukemia ( Chen et al, 2023 ), type 2 diabetes ( Li and Li, 2023 ), and esophageal cancer ( Wang et al, 2024 ), but they have yet to be studies in the context of mental health disorders. However, multiple clinical studies have demonstrated that psychological distress and mental illness, such as depression and anxiety, are associated with alterations in the abundance of Ruminococcaceae family members ( Chen et al, 2021 ; Chin Fatt et al, 2023 ), and animal studies have suggested that regulating the abundance of Ruminococcaceae family members with various interventions can promote the production of SCFAs and other neurochemical-related metabolites.…”
Section: Discussionmentioning
confidence: 99%